2012
DOI: 10.1089/ars.2011.4277
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic Mitochondrial Pathology in Alzheimer's Disease

Abstract: Significance: Synaptic degeneration, an early pathological feature in Alzheimer's disease (AD), is closely correlated to impaired cognitive function and memory loss. Recent studies suggest that involvement of amyloid-beta peptide (Ab) in synaptic mitochondrial alteration underlies these synaptic lesions. Thus, to understand the Abassociated synaptic mitochondrial perturbations would fortify our understanding of synaptic stress in the pathogenesis of AD. Recent Advances: Increasing evidence suggests that synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(94 citation statements)
references
References 92 publications
2
92
0
Order By: Relevance
“…FUS is a DNA-and RNA-binding protein that contributes to DNA damage repair, mRNA splicing, and microRNA (miRNA) biogenesis. l An expansion of GGGGCC repeats in the noncoding region of the C9orf 72 gene results in the production of neurotoxic dipeptide repeat proteins such as poly(Gly-Ala), poly(Gly-Pro), poly(Gly-Arg), poly(Pro-Arg), and poly(Pro-Ala) in motor neurons ◂ signaling (Du et al 2012). Cyclophilin D (CypD), a subunit of the mitochondrial permeability transition pore, has been suggested to function as an Aβ receptor in mitochondria (Baines et al 2005;Du et al 2008).…”
Section: Mapk Signaling In Neurodegenerative Diseasesmentioning
confidence: 99%
“…FUS is a DNA-and RNA-binding protein that contributes to DNA damage repair, mRNA splicing, and microRNA (miRNA) biogenesis. l An expansion of GGGGCC repeats in the noncoding region of the C9orf 72 gene results in the production of neurotoxic dipeptide repeat proteins such as poly(Gly-Ala), poly(Gly-Pro), poly(Gly-Arg), poly(Pro-Arg), and poly(Pro-Ala) in motor neurons ◂ signaling (Du et al 2012). Cyclophilin D (CypD), a subunit of the mitochondrial permeability transition pore, has been suggested to function as an Aβ receptor in mitochondria (Baines et al 2005;Du et al 2008).…”
Section: Mapk Signaling In Neurodegenerative Diseasesmentioning
confidence: 99%
“…2 Even though a precise mechanism of Aβ-induced toxicity has not been fully understood, several studies have reported synaptic and mitochondrial Aβ accumulation and dysfunction in early stages of AD development. [2][3][4] Furthermore, it has been described that Aβ interacts with various mitochondrial proteins, resulting in enhanced oxidative stress, energy misbalance and overall cell toxicity.…”
mentioning
confidence: 99%
“…The association between impaired mitochondrial performance and the development of synaptic dysfunction is not unexpected as these organelles are involved in every stage of neurotransmission including the synthesis and storage of neurotransmitters, the trafficking and recycling of synaptic vesicles (SVs), presynaptic neurotransmitter release, neurotransmitter synthesis, calcium ion homeostasis as well as supplying ATP and regulating levels of ROS [240][241][242].…”
Section: Oxidative Stress and The Development Of Synaptic Dysfunctionmentioning
confidence: 99%